Implementation’S Facilitators and Barriers of the Chilean Skills for Life Program According to the Consolidated Framework for Implementation Research; [Facilitadores y Barreras Para la Implementación del Programa Chileno Habilidades Para la Vida Según el Marco Consolidado Para la Investigación de la Implementación] - Rojas-Andrade, R; Prosser-Bravo, G (Universidad de Tarapaca, 2024)
Background: The HPV-Junaeb program is the most important school-based mental health program in Chile, aiming to improve students’ essential life skills to face life adversity and promote successful academic trajectories. However, effective implementation faces various challenges and is influenced by multiple factors. Understanding these barriers and facilitators is essential for the program’s success and sustainability. Aim: To identify the barriers and facilitators affecting the implementation of the HPV-Junaeb program from the perspectives of national, regional, and local institutional leaders and coordinators. Methods: Interviews with 16 program coordinators were conducted using the Consolidated Framework for Implementation Research model. This model groups implementation factors into five dimensions: characteristics of the innovation, external context of the implementing institution, internal context of the institution, characteristics of the individuals, and the implementation process. The interviews were followed by a deductive content analysis, classifying factors according to their contribution to implementation (facilitator [+] or barrier [–]) and their impact on it (2 = strong; 1 = weak; 0 = neutral). Results: Strong facilitators identified included the training of professionals responsible for program execution, active participation of students and the community, and the adaptation of the program to local needs and specificities. Strong barriers identified included cultural resistance to mental health care and the work of psychologists, low institutional resources and support, and weak coordination among various stakeholders. Conclusion: The study concludes that the program’s characteristics and its execution process are strong facilitators. In contrast, external contextual factors act as significant barriers to implementation. Continuous program evaluation is crucial to ensure its effectiveness and adaptability to diverse contexts. © 2024, Universidad de Tarapaca. All rights reserved.